Kaligrafi Kufi dan Strategi Pengembangan Kecerdasan Visual Spasial - Jamaluddin Shiddiq (Qolamuna : Jurnal Studi Islam, 2021)
Abstract The purpose of this study was to know the implementation strategy of Kufi calligraphy teaching that had an impact on the development of visual-spatial intelligence at MI Ma'arif Setono Ponorogo. This type of research is included in the field research with a descriptive-qualitative approach. Data collection uses observation, interviews and documentation methods, while data analysis uses data reduction techniques, presenting data and drawing conclusions. The results showed that visual-spatial intelligence could be developed through several strategies, there are: art activities, drawing and painting, introducing colouring techniques, recognize the basic geometry, making handicrafts, invite them to recognize objects and rooms around them, and introduce navigation. Keyword : Kufi calligraphy, teaching, visual-spatial intelligence